The profile and persistence of clinically critical antibiotic resistance genes and human pathogenic bacteria in manure-amended farmland soils - Zhu, Lin; Lian, Yulu; Lin, Da; Lin, Guoping; Wang, Meizhen (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Microbial contamination in farmlands is usually underestimated and understudied. Different fertilization times and manure origins might introduce and change the microorganism diversity in farmland soils and thus might influence the abundance and persistence of microbial contamination including antibiotic resistance genes (ARGs), human bacterial pathogens (HBPs), and virulence factor genes (VFGs). Methods A 0.5-/1.5-year fertilization experiment was performed, and metagenomic sequencing was conducted to quantify microbial contamination. The resistomes of soil samples revealed that ARGs against antibiotics which were extensively used in veterinary medicine as well as clinically critical ARGs (CCARGs) persisted in manure-amended soils. Here the extended-spectrum beta-lactamase and carbapenemase bla genes, the high-level mobilized colistin resistance gene mcr, the tigecycline resistance gene tet(X), and the vancomycin resistance gene van, all of which can circumvent the defense line of these “last-resort” antibiotics were selected to investigate CCARG pollution in farm environments. Results A total of 254 potential HBPs and 2106 VFGs were detected in soil samples. Overall, our results revealed that (1) farmland soils could serve as a reservoir of some important bla, mcr, tet(X), and van gene variants, (2) the diversity and relative abundance of HBPs and VFGs increased significantly with incremental fertilization times and were discrepant among different manureamended soils, and (3) most CCARGs and VFGs coexisted in HBPs. Disscusion The results of this study suggested a biological risk of manure in spreading antimicrobial resistance and pathogenicity.